2019
DOI: 10.4103/ajns.ajns_201_19
|View full text |Cite
|
Sign up to set email alerts
|

X-ray and computed tomography scan-based morphometric analysis of skull baselines in Indian population

Abstract: Introduction:The study aims at providing an overview of morphometric measurements of the skull baselines in normal Indian population and compares these dimensions with those of other races and ethnicities. This study will help in defining “normal” baseline values for Indian population. It will also compare dimensions as measured on X-ray and computed tomography (CT) scan to assess the reliability of X-ray as a diagnostic modality for the assessment of the skull baselines in Indian population.Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
3
1
Order By: Relevance
“…18 Although male-female difference was found to be significant in the AADI and PADI parameters in the present study, seldom was any such difference recorded in the other studies. 5,13,[16][17][18][19]21,22 Similar to our study, Gupta et al, and Tanrisever et al, also found a significant difference between males and females when PADI was scrutinized (males had higher values). 18,19 Chen et al, found a statistical significance between males and females when AADI was examined (males had higher values).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…18 Although male-female difference was found to be significant in the AADI and PADI parameters in the present study, seldom was any such difference recorded in the other studies. 5,13,[16][17][18][19]21,22 Similar to our study, Gupta et al, and Tanrisever et al, also found a significant difference between males and females when PADI was scrutinized (males had higher values). 18,19 Chen et al, found a statistical significance between males and females when AADI was examined (males had higher values).…”
Section: Discussionsupporting
confidence: 88%
“…21 Alike to the findings of Dash et al, and Marathe et al, our study also showed no differences between genders when examining dMR, dMG, dCL, and CCA. 16,17 After analyzing the data and comparing our results with that of the other races, we conclude that the data mentioned in the literature are not on par with what was observed in the present study. Although the values varied within the normal range, achieving nil statistical significance between the same and other populations may prove challenging.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations